Ethnobotanical Study of Plants Used For The Wedding Ceremony in The Boyolangu Subdistrict, Tulungagung District, East Java Province - Nursita, Dwi Candra; Amalia, Denis; Minarno, Eko Budi (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2020)
Javanese ethnic still upholds local wisdom including marriage customs. Traditional wedding ceremonies inherited from ancestors are still practiced up to present in the Boyolangu subdistrict, Tulungagung District, East Java Province. Traditional wedding ceremonies in this area are often carried out by utilizing plants during the procession, especially at the procession ofÂ temu manten.Â The use of plants in this procession is closely related to ethnobotany. Ethnobotany is an ecological discipline and the principle of the community's conception of local plants sources that can be used as a protector of cultural values. This research aims to find out the types of plants that are used as in the traditional wedding ceremonies and to provide an understanding of conservation of certain plants typically used for traditional wedding ceremonies. This research used quantitative descriptive design and applied a purposive sampling technique. It involved 10 respondents of community and 1 key informant (dukun manten or shaman). Based on the results of the study, the community in this area uses a total of 14 species of plants of 11 families at a traditional wedding ceremony. Commonly, the community utilizes the leaves and other parts of plants such as fruit, seeds, stems, and flowers. They are directly arranged in a certain way and used. The plants are obtained from around the yards of the communityâ€™s house